Prevalence of hepatitis B surface antigen (HBsAg) positivity and its associated factors in Rwanda - Jean Damascene Makuza; Jean Olivier Twahirwa Rwema; Corneille Killy Ntihabose; Donatha Dushimiyimana; Justine Umutesi; Marie Paul Nisingizwe; Janvier Serumondo; Muhamed Semakula; David J. Riedel; Sabin Nsanzimana (BMC Infectious Diseases, 2019)
Abstract Background The epidemiology of hepatitis B virus (HBV) infection in the general population in Rwanda is not well known. This study examined the prevalence of HBV surface antigen (HBsAg) positivity and associated risk factors among people aged 25 years and over in an organized national screening campaign. Methods This is a cross-sectional study using data from a nationwide HBV screening campaign organized by the Rwanda Biomedical Centre from March to October 2018. This campaign targeted individuals aged > 25 years old from 24 of 30 districts of Rwanda. Sensitization was done through multimedia announcements, community health workers and local church leaders. During the campaign, a structured interview was administered by trained healthcare workers to collect information on socio-demographic, clinical and behavioral characteristics of participants; HBV screening was performed with HBsAg using enzyme-linked immunosorbent assays (ELISA) testing. Bivariate and multivariate logistic regressions were used to assess factors associated with HBsAg positivity in the screened participants. Results A total of 327,360 individuals were screened during the campaign. Overall 12,865(3.9%) were HBsAg positive. The highest prevalence (4.2%) was found in the 35–44-year-old group, but the difference from other groups was not significant (Odds Ratio [OR = 1.057, 95% Confidence Interval(CI) (0.904–1.235)]. Being male [OR = 1.348, 95% CI (1.30,1.40)]; being single [OR = 1.092, 95% CI (1.10–1.16)] compared to married; a previous positive TB screening test [OR = 2.352, 95% CI (1.63–3.39)]; history of surgical operation [OR = 1.082, 95% CI (1.00,1.17)]; exposure to traditional operational practices and scarification [OR = 1.187, 95% CI (1.13, 1.24)]; and having a person in the family with viral hepatitis [OR = 1.367, 95% CI (1.21, 1.53)] were significantly associated with HBV infection. Conclusions These data provide the first national estimate of the prevalence of HBsAg seropositivity and its associated factors in Rwanda. The study identified people with the highest risk of HBV infection who should be the priority of future prevention efforts in Rwanda and in similar settings.